DESTRUCTION OF SOIL COATERS - Abdurakhmonov, Urol (Innovatsion texnologiyalar, 2024)
The article determines the speed of movement of the ripper to ensure crumbling of soil lumps lying on the surface of the field during surface tillage. The destruction of soil lumps lying on the soil surface occurs as a result of the impact of the ripper teeth. In this case, the probability of destruction and the degree of crumbling of lumps depends on the loss of kinetic energy when the ripper teeth collide with lumps of soil, since this energy is spent on their deformation, i.e. for crumbling lumps. This means that the greater the energy loss during impact, the better the degree of crumbling of lumps. With increase the speed of movement of the unit, the energy spent on the destruction of lumps increases, and therefore the quality of their crumbling improves. In addition, analysis of the expression shows that the destruction of lumps and the required degree of their crumbling can be achieved mainly by choosing the speed of movement of the ripper. Taking this into account, the minimum (critical) speed of movement of the unit was determined, at which crumbling of soil lumps located on the surface of the field is ensured. From the above studies it has been established that in order to ensure crumbling of soil lumps, the speed of movement of the ripper must be at least 2.0 m/s.